Case Study : Saudi Arabian Airlines Catering Focusing On In-Flight Catering Business - Abotalib, Reem Hassan (2008)
Saudi Catering has progressively grown into one of the foremost airline catering in the Middle East region, and in the world of aviations' catering. Saudi Arabian Airlines catering has transformed recently from being a governmental owned to a joint stock, with Saudi Arabian Airlines (Government) holding 51% and Strategic Catering Companies, (Corporate) holding 49%.